2013
DOI: 10.1177/1077559513487944
|View full text |Cite
|
Sign up to set email alerts
|

Affective Facial Expression Processing in 15-Month-Old Infants Who Have Experienced Maltreatment

Abstract: This study examined the neural correlates of facial affect processing in 15 month-old maltreated and nonmaltreated infants. Event-related potentials (ERPs) were elicited while infants passively viewed standardized pictures of female models posing angry, happy, and neutral facial expressions. Differences between maltreated (N=25) and nonmaltreated (N=20) infants were observed on three ERP components: P1, P260, and Nc. Compared to nonmaltreated infants, maltreated infants had greater P1 amplitude in response to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
33
0
5

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 82 publications
5
33
0
5
Order By: Relevance
“…Over the past several decades, a number of studies have found considerable importance for the consequences of maltreatment that occurs during the early years of life (Cicchetti, Rogosch, Gunnar, & Toth, 2010; Curtis & Cicchetti, 2013; Dunn, McLaughlin, Slopen, Rosand, & Smoller, 2013; Kaplow & Widom, 2007; Manly, Kim, Rogosch, & Cicchetti, 2001). This research on the effects of early child maltreatment has important implications for understanding the process of brain development.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past several decades, a number of studies have found considerable importance for the consequences of maltreatment that occurs during the early years of life (Cicchetti, Rogosch, Gunnar, & Toth, 2010; Curtis & Cicchetti, 2013; Dunn, McLaughlin, Slopen, Rosand, & Smoller, 2013; Kaplow & Widom, 2007; Manly, Kim, Rogosch, & Cicchetti, 2001). This research on the effects of early child maltreatment has important implications for understanding the process of brain development.…”
Section: Discussionmentioning
confidence: 99%
“…Several other studies using event-related potentials and behavioral evidence have found a sensitivity bias to perceive anger in physically abused children (Pollak & Sinha, 2002; Pollak, Vardi, Pultzer-Bechner, & Curtin, 2005; Shackman, Shackman, & Pollak, 2007) and, more generally, in a sample of maltreated children (Curtis & Cicchetti, 2011, 2013; Leist & Dadds, 2009; Masten et al, 2008; Pollak, Klorman, Brumaghim, & Cicchetti, 2001). In an attempt to explain these findings, Pollak et al (2005) suggested that in abusive home environments children learn to associate anger with threat of harm and therefore, they are hypervigilant to anger in their environment.…”
Section: Childhood Maltreatment and Emotion Processingmentioning
confidence: 93%
“…Studies using a range of behavioural and electrophysiological testing paradigms with maltreated children and adolescents suggest that various forms of early adversity are associated with long‐term impairments in the threat‐ and fear‐processing systems. These changes are detectable as early as 15 months, and include preferential attention to threatening information, heightened neural response to negative stimuli and enhanced perceptual ability for cues associated with danger, such as angry faces (Curtis & Cicchetti, ; Pollak & Sinha, ; Pollak & Tolley‐Schell, ; Pollak, Vardi, Putzer Bechner, & Curtin, ). Animal data also point to the existence of a causal link between early adverse experiences (such as reduced maternal care) and long‐lasting neurophysiological changes in brain regions, such as the amygdala, striatum and hippocampus, involved in threat detection and stress responses (Caldji, Diorio, & Meaney, ; Caldji et al., ; Meaney, ).…”
Section: Functional Magnetic Resonance Imaging and The Study Of Childmentioning
confidence: 99%